MicroRNAs and Presbycusis - Hu, Weiming (Aging Dis, 2018)
Presbycusis (age-related hearing loss) is the most universal sensory degenerative disease in elderly people caused by the degeneration of cochlear cells. Non-coding microRNAs (miRNAs) play a fundamental role in gene regulation in almost every multicellular organism, and control the aging processes. It has been identified that various miRNAs are up- or down-regulated during mammalian aging processes in tissue-specific manners. Most miRNAs bind to specific sites on their target messenger-RNAs (mRNAs) and decrease their expression. Germline mutation may lead to dysregulation of potential miRNAs expression, causing progressive hair cell degeneration and age-related hearing loss. Therapeutic innovations could emerge from a better understanding of diverse function of miRNAs in presbycusis. This review summarizes the relationship between miRNAs and presbycusis, and presents novel miRNAs-targeted strategies against presbycusis.